PEMBUATAN PROGRAM APLIKASI PENJUALAN INVENTORY DAN PENGIRIMAN BARANG BERBASIS WEB PADA DUNIA MEGA DIGITAL - Bernard Dean Sofli; Tony Tony; Desi Arisandi (Jurnal Ilmu Komputer dan Sistem Informasi, 2014)
Dunia Mega digital is a company engaged in selling digital printing services, in this case the services offered in the form of brochures, banners,  and the others are related to digital printing. Currently Dunia Mega Digital doesn’t have a computerized system to support the company’s performance.  The main purpose of the system sales, inventory, and delivering is to increase performance of sales marketing. The advantages of this project are customer can order product without meet the company, also can order anytime he want. This system is made from SDLC method containing planning, analysis, design, implementation, testing, and maintenance. Key wordsPenjualan, inventory, tawar online, Percetakan, Digital Printing